Federal funds for day care projects - Women's Bureau (DOL), Washington, DC.; Women's Bureau (DOL), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
"day care" provides care, guidance, and supervision for children away from home during the day. Funds for day care projects are available from a number of federal agencies and may be used for providing direct care of children in day care facilities, training personnel, and supporting research and demonstration projects relating to various aspects of day care. Specific grant or loan programs for day care projects of the department of health, education, and welfare, the office of economic opportunity, the department of housing and urban development, the Department of Labor, small business administration, and the department of agriculture are listed. For each program, information is included with respect to statutory authority, eligibility requirements, proportion of federal funds that may be granted or limit on funds that may be lent, review procedures, and sources of further information. (ps)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Agencies; Day Care; Directories; Federal Aid; Federal Programs; Projects